1992
DOI: 10.1007/bf01323999
|View full text |Cite
|
Sign up to set email alerts
|

Food commercials during television soap operas: What is the nutrition message?

Abstract: Studies have examined food commercials appearing during daytime, prime time, and Saturday morning programming; none have evaluated commercials aired during soap operas. The purposes of this study were to examine the dietary composition of food products advertised during soap operas and the health and nutrition claims made on their behalf, using current dietary recommendations as a basis of evaluation. A total of 508 commercials videotaped during the top nine daytime serials for five consecutive days, were for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Constant commercial advertisements accompanied by prolonged TV watching may lead to unhealthy eating patterns such as snacking, which typically involves a higher caloric intake than do more healthy eating habits [18-20]. This change to an unhealthy diet including low fiber intake, a lack of fruits and vegetables, increased sugar, and more convenience food is also widely believed to have contributed to the child obesity epidemic [21].…”
Section: Discussionmentioning
confidence: 99%
“…Constant commercial advertisements accompanied by prolonged TV watching may lead to unhealthy eating patterns such as snacking, which typically involves a higher caloric intake than do more healthy eating habits [18-20]. This change to an unhealthy diet including low fiber intake, a lack of fruits and vegetables, increased sugar, and more convenience food is also widely believed to have contributed to the child obesity epidemic [21].…”
Section: Discussionmentioning
confidence: 99%
“…For example, television advertising might influence both the quality and quantity of food consumed. Lank et al (1992) reported that 58% of food advertised on television during the afternoon were high in fat. Food cues are also evident during popular viewing times and in advertisements (Story & Faulkner, 1990), and these cues may exert a greater influence in the obese (Falciglia & Gussow, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…46 -52 A recent prospective study on women has shown that watching television was associated with a significantly increased risk of diabetes mellitus (each 2-hour-per-day increment in time spent watching television was found associated with a 14% increase in diabetes risk) and obesity. 53 This was felt to be because television watchers exercise less, 50,51 eat more, 54,55 and eat unhealthy 53 (because of commercials appearing on the television). Adaptation of such behavior has serious consequences for South Asians, who already are genetically predisposed to metabolic syndrome.…”
Section: Change In Diet and Exercise Patternsmentioning
confidence: 93%